Mengintegrasikan AI dalam Pembelajaran Al-Qur'an: Analisis Potensi, Tantangan, dan Solusi - Ahmad Mahfud; Nurul Hamidah; Surya Saputra Mahmud; Abd. Kholid (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
The rapid advancement of Artificial Intelligence (AI) has created new opportunities to transform Qur'anic learning through more adaptive, interactive, and accessible educational approaches. This study aims to analyze the potential, challenges, and possible solutions for integrating AI into Qur'anic learning. A qualitative approach was employed using library research and an exploratory study, with data collected from scientific publications and case analyses of AI-powered Qur'anic learning applications, including Ngaji.ai and Tarteel. The findings indicate that AI offers significant potential to personalize learning experiences, expand learning accessibility, provide real-time recitation feedback, support interactive learning environments, and utilize learning analytics to monitor students' progress. Nevertheless, its implementation is constrained by several challenges, including limited digital literacy among teachers, inadequate technological infrastructure, ethical and theological concerns, and the potential decline of direct teacher–student interaction. Therefore, successful AI integration requires comprehensive strategies involving teacher capacity building, infrastructure development, the establishment of a Sharia-compliant AI ethical framework, the adoption of hybrid learning models, and continuous research to ensure that AI enhances Qur'anic learning while preserving educational quality and Islamic values.